IPR 100 - Rustic dwarf Arabica coffee cultivar with resistance to nematodes Meloidogyne paranaensis and M. incognita - Sera,Tumoru (2017)
Abstract ‘IPR 100’ was derived from a crossing between “Catuaí” and a hybrid (“Catuaí” x BA-10 coffee). ‘IPR 100’ is a medium size dwarf cultivar with high rusticity, with late ripening cycle, and with resistance to Meloidogyne paranaensis and to some M. incognita populations.